A report on Petang Island Resort ‘the effectiveness of marketing strategies’ / Ghani Omar, Syahrul Hezrin Mahmud and Najdah Abd Aziz - Omar, Ghani; Mahmud, Syahrul Hezrin; Abd Aziz, Najdah (Pusat Pendidikan Lanjutan, UiTM, 2007)
The intensive promotional effort about Tourism Malaysia, particularly in the Asia Region, has contributed to the rebound of 1.5 Million tourist arrivals in 2004. This figure has increased from year to year .Based on this figure, the high percentage of tourist arrival in Malaysia are from ASEAN countries followed by China, Japan, Korea, United Kingdom, USA, European Union Countries ( EU ), Australia and New Zealand. Besides, there are also tourist from West Asia and Gulf States such as Kuwait, Saudi Arabia, Egypt, Bahrain and United Arab Emirates ( UAE). In spending holiday, resorts are to be the first choice by the tourist in spending their vacation compared to hotels. Some tourists prefer to stay in resorts because of the reasonable, attractive packages, nice and exclusive location. Resorts are normally located at strategic and beautiful places such as near the beach, in the park and even near the river or hills. It is relevance with the main purpose of it existence where to provide natural site and harmonious place to the visitors. The objective of this research is to analyze the marketing strategies implemented by Petang Island Resort (PIR) and then to determine the effectiveness and efficiencies of those strategies. At the end of the research, the researchers will come out with suggest solution in order to improve PIR performance. Due to this scenario, PIR takes positive steps in providing a good place and service to guess either local or foreign tourist. So PIR should expose itself to the market by using effective marketing strategies. For this purpose, PIR has to come up with attractive promotional strategy in order to introduce the place to local and international tourists. In general, the findings of this research show that there were ineffective of marketing strategies especially due to the poor promotional strategy. The researchers had suggested appropriate marketing strategies that PIR should adopt for its improvement. It is also important to consider about the marketing mix ( 4 Ps ) which is product, place, price and promotion in running the business activities.